2013
DOI: 10.1002/jbio.201200228
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐wavelength excitation for fluorescence‐based quantification of zinc protoporphyrin IX and protoporphyrin IX in whole blood

Abstract: Journal of BIOPHOTONICSQuantification of erythrocyte zinc protoporphyrin IX (ZnPP) and protoporphyrin IX (PPIX), individually or jointly, is useful for the diagnostic evaluation of iron deficiency, iron-restricted erythropoiesis, lead exposure, and porphyrias. A method for simultaneous quantification of ZnPP and PPIX in unwashed blood samples is described, using dual-wavelength excitation to effectively eliminate background fluorescence from other blood constituents. In blood samples from 35 subjects, the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Washing the red blood cells is known to improve the precision of measurements by the conventional haematofluorometer 24 , but requires additional laboratory facilities and trained personnel. As shown in a previous study, the dual-wavelength excitation method effectively reduces plasma bilirubin fluorescence 19 . The spectral fitting algorithm, by eliminating unstructured background fluorescence in the difference spectrum, likely suppresses interference from medications and other components in the plasma or bound to erythrocyte membranes, but this effect has not been systematically examined.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Washing the red blood cells is known to improve the precision of measurements by the conventional haematofluorometer 24 , but requires additional laboratory facilities and trained personnel. As shown in a previous study, the dual-wavelength excitation method effectively reduces plasma bilirubin fluorescence 19 . The spectral fitting algorithm, by eliminating unstructured background fluorescence in the difference spectrum, likely suppresses interference from medications and other components in the plasma or bound to erythrocyte membranes, but this effect has not been systematically examined.…”
Section: Discussionsupporting
confidence: 60%
“…To quantitatively extract the zinc protoporphyrin fluorescence in the presence of this very large background, we acquire additional fluorescence spectra excited at a wavelength of 407 nm (ref. 19 ). Both spectra are obtained with an excitation power of ∼2.5 mW for the illuminated area of 1-mm diameter to comply with the light-exposure limits defined by the international standard IEC 60825-1:2014.…”
Section: Resultsmentioning
confidence: 99%
“…The application of dual-wavelength excitation in the HF technique [24] allowed the recording of background fluorescence, which then could be removed from the analyte spectra [27]. In 2019, it was shown that even the non-invasive measurement of erythrocyte ZnPPIX in children and women after childbirth was possible on the wet vermillion of the lower lip using this principle [28,29].…”
Section: Spectrophotometry and -Fluorometrymentioning
confidence: 99%
“…Notably, our TIRF study, carried out with an excitation wavelength of 405 nm, reveals the emergence of autofluorescence in dried smears. This wavelength was chosen to be in resonance with the strongest absorption peak in protoporphyrin IX, which plays an important part in the biosynthesis of heme [15,16]. Our measurement samples were parasite enriched smears on cover slips, which were prepared from cultures treated with Percoll (see ).…”
Section: Morphological Changes In Infected Rbcsmentioning
confidence: 99%